White-light emitting multi-lanthanide terephthalate thin films by atomic/molecular layer deposition - Ghazy Amr; Lastusaari Mika; Karppinen Maarit (ROYAL SOC CHEMISTRY, 2025)
Precisely composition-tuned white-light-emissive lanthanide-organic thin films are fabricated using the combined atomic/molecular layer deposition (ALD/MLD) technique. The emission colour characteristics are comparable (and even exceeding) to those measured for commercial incandescent bulbs, fluorescent tubes and LED lamps. The films are composed of up to four lanthanide species (La, Er, Tb, and Eu) and terephthalate as the organic linker molecule. Terephthalate plays multiple roles in the films, as it not only brings mechanical flexibility to the films and defines the distance between the lanthanide ions, but also shows upon UV excitation UV/blue broad-band emission around 300-450 nm. This excitation energy was found to be efficiently transferred to the Er3+ ions, such that the emission could be shifted to the longer wavelengths. Then, Tb and Eu provide the green and red emissions, such that the films in overall show warm white light emission. Finally, using a three-layer composition to control the distribution of the Ln dopants, the emission intensity was increased fourfold.